Demand Analysis for Solid Fuel and Its Substitutes as Domestic Energy in Imo State, Nigeria: Application of Quadratic Almost Ideal Demand System (QUAIDS) - Chukwuemeka, Ehirm Nnamdi; Osuji, Emeka Emmanuel (Finance & Economics Review, 2020)
Purpose: This study aims to model the demand analysis for solid fuel and its substitute for domestic cooking energy among households in Imo State. Methods: Data on socio-economic characteristics of the respondents, monthly expenditure on energy used for domestic cooking, unit prices, and quantity of different energy sources were collected using a multi-stage sampling technique from 262 households I Imo State. Data were analyzed using descriptive, quartile distribution and QUAIDS inferential statistics to achieve the objectives of the study. Results: The empirical analysis of the demand for household energy usage revealed that the quadratic expenditure term is statistically significant in firewood, sawdust, and wood-shaving expenditure share equations. It implies that their null hypothesis of expenditure linearity is strongly rejected. Furthermore, the prices and demographics of the household head significantly influence the budget shares of the different energy used. Expenditure elasticity of all the energy sources are elastic. Own price (Marshallian and Hicksian) of firewood, sawdust, and kerosene are price elastic while charcoal and wood-shaving are price inelastic. The Uncompensated Marshallian’s cross elasticity of almost all energy sources are complementary. However, the result of the compensated- Hicksian’s cross elasticity values indicated that almost all the energy uses are substitutable except for firewood – charcoal, firewood-wood shaving, firewood-kerosene, and sawdust-wood shaving that are complementary. Implications: The result indicates that the timber products and its substitutes demand domestic cooking follow both energy ladder and stacking principles as households can quickly switch to a better energy source at the same time exhibit their dynamism in the ability to combine both traditional and modern fuels to meet their domestic energy needs based on price and affordability. The study, therefore, recommends that younger females in the household should be targeted in demonstrating the demand for cleaner energy using educational facilities and reduction in unit prices of such energy in the area.